PROSPECTIVE SOFTWARE TOOLS FOR DATA ANALYSIS IN BUSINESS - LISHCHYNSKA, LYUDMYLA; DOBROVOLSKA, NATALIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article presents the results of a research of promising software tools for data analysis that can be used for domestic business, their characteristics, identifying features, advantages and disadvantages of various business intelligence tools, recommendations for implementation. Data analysis tools provide an opportunity to significantly improve the company’s performance, but only when the selection of the tool, its implementation and maintenance take into account all the features of the company’s business processes. Business analytics software tools help you analyze your datasets to make informed management decisions, improve processes, and shape and achieve business goals.To choose the right business intelligence tools, you need to consider the most important factors: visual functionality, flexibility, integration, customization, mobility, learning requirements, pricing, IT support, cloud or local BI deployment, and more. In addition, you need to identify the functions that are most important to your company, will allow you to get a balanced option: meet current needs and anticipate further growth. The main functions offered by BI suppliers: debugging information panels; built-in analytics; functions of joint work; remote access by mobile devices; independent data preparation; advanced analytics, etc. Areas of use of data mining are virtually unlimited, in particular, its use by commercial enterprises that implement projects based on information repositories can gain significant advantages over competitors, as well as in strategic planning. Data is a powerful tool for business transformation, forcing companies to use modern business intelligence tools and seek experts to help understand, decipher and interpret hidden trends in the industry and the market. This is especially true when working with Вig data.